Chronic post-surgical pain after knee arthroplasty: a role of peripheral nerve blocks - Sreckovic, Svetlana; Ladjevic, Nebojsa; Milicic, Biljana; Tulic, Goran; Milovanovic, Darko; Djukanovic, Marija; Kadija, Marko (Frontiers in Medicine, 2024)
Introduction: Peripheral nerve blocks are an efficient method of pain control after total knee arthroplasty (TKA), but there is no report of their impact on chronic post-surgical pain (CPSP). Methods: This prospective observational study aimed to assess adductor canal block (ACB) and IPACK block (blocks vs. no blocks) on opioid consumption, postoperative pain score, chronic post-surgical pain two years after TKA. Results: 166 patients (82 vs. 84) were analyzed. Opioid consumption was less in the group with blocks (9.74±3.87mg vs 30.63±11.52mg) (p<0.001). CPSP was present in 20.24% of patients in the group without blocks and 6.1% of patients with blocks (p=0.011). Predictor variables of CPSP included pain before surgery (cut-off of 5.5), pain at rest (cut-off of 2.35), pain during active movement (cut-off: 2.5), and opioid consumption (cut-off: 8 mg). Conclusion: Peripheral nerve blocks provide adequate analgesia, significantly decrease opioid consumption, improve functional outcomes, and reduce CPSP two years after surgery.